Pengaruh Pemberian Pupuk Hayati Mikoriza Dan Rock Phosphate Terhadap Pertumbuhan dan Produksi Tanaman Jagung Manis (Zea Mays Saccharata Sturt) - Hartanti, Ima; Yoseva, Sri; ', Hapsoh (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
The aim of this research are to determine the effect of mycorrhizal biofertilizer, rock phosphate and interaction on growth and yield of sweet corn (Zea mays saccharata Sturt). This research was conducted experimentally by using Randomized Design Group (RDG) factorial with two factors namely mycorrhizal biofertilizer and rock phosphate with 3 replications. The parameters focus on plant height, the number of leaves, leaf weight, trunk diameter, when the pistil appear, when the pollen arise, harvest age, cob weight per cornhusk/m2, cob weight without cornhusk/m2, cob diameter, cob length, the number of rows per cob and the percentage of infected mycorrhizal roots.The result of this research shows that the interaction of mycorrhizal biofertilizer and rock phosphate and the main factor rock phosphate there is no real effect to all the parameters, whereas the main factor mycorrhizal biofertilizer significantly effect the parameters of trunk diameter, cob length, and percentage of mycorrhizal infected roots. Fertilizing of mycorrhizal biofertilizer can increase cob weight per cornhusk/m2 as 17.9% than without fertilizing it. Keywords : Sweet corn, mycorrhizal biofertilizer, rock phosphate